The cowboy's deadly reunion - Dees, Cindy (Dees, Cindy. Runaway Ranch., 2021)
"When Wes Morgan rescued his boss's rebellious daughter, her lies destroyed his career in the Navy. Months later, Jessica has arrived at his Montana ranch...and she needs the Marine-turned-cowboy's protection. Someone wants both her and Wes dead. Much as he can't handle Jessica, Wes can't refuse the city slicker's need or deny their still-sizzling attraction. Can they get past their tempestuous history...alive?."--Back cover.